La réflexivité dans la formation des enseignants-chercheurs : quelle place dans leur développement professionnel? - Julitte Huez
The literature on teacher training and professional development refers to reflexivity as an essential element in understanding their work. Thus, when the training of higher education teachers in their teaching practices is structured, reference is made to the reflective approach. However, what does this mean for teacher-researchers (TR), trainers and even decision-makers?Our research is based on the field of the Université Fédérale Toulouse Midi-Pyrénées and more particularly on the training of TR by higher education trainers. It proposes, around this notion of reflexivity, to analyze the perceived gap between the intention of implementation and what is realized.After resituating the context of TR training, which has become prescribed, we analyze how it is proposed to develop a reflective posture. To do so, we rely on resources made available to them, such as training programs and benchmarks for the practice of the TR profession. We then present an example of a system set up at the local level as part of our research. This GEASE (Groupe d'entraînement à l'analyse de situations éducatives), which sees its initiation subject to a professional proximity between TR and trainer/researcher, creates a space where reflective practice is possible. It also brings to light, through the expression of the TR, the profession experienced, and this, in its entirety. What they say questions the relevance of the training and draws its limits.